Covid-19 Vaccine: Global Stock Market “Game Changer” - Hartono, Hartono (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
This research is a conceptual paper that examines the impact of the presence of the Covid-19 vaccine on investor sentiment and the performance of the global stock market after being hit by high concerns due to the pandemic. The results showed that each stage of vaccine development received high appreciation from stock investors, especially after vaccine candidates passed clinical trials in humans. Investors' positive sentiment towards the vaccine program boosted stock market performance. However, the sentiment of this vaccine cannot stand alone, it needs government policy support to truly restore market confidence in the recovery of social and economic conditions, including the stock market. This research combines secondary data published from high-ranking journals that can be used to help develop future tests.